Factors influencing international tourists’ decision to revisit Jordan as a MICE destination - Al Ramadan, Ammar Mohammad Mahmoud (2024)
The failure of many developing countries such as Jordan in obtaining profit from the tourism industry, actually stems from the lack of understanding on the factors that influence the international tourists’ intention to revisit the country especially in the Meetings, Incentives, Conferences, and Exhibitions (MICE) tourism segment. In order to narrow this knowledge gap, this study aims to examine the causal association between push factors, namely networking opportunities (NO) and educational opportunities (EO), and the pull factors which include destination image (DI), travel cost (TC), destination attraction (DA), and accessibility (AC) with revisit intention (RI) among international MICE tourists in Amman, Jordan. This study also examines the moderating effects of safety and security (S/S) and travel experience (TE) on these relationships. A quantitative research method with deductive approach was employed in this study. Data were collected through survey method where 600 survey questionnaires were distributed to international MICE tourists who have attended 12 international MICE events held in Amman, Jordan. 479 survey questionnaires were valid for further analysis. Partial Least Squares Structural Equation Modelling (PLSSEM) was utilised to test the hypotheses. The results indicate a positive and significant relationship between push factors (NO and EO), and pull factors (DI, TC, DA, AC), with revisit intention. The analysis also reveals that safety and security (S/S) significantly moderates the relationship between NO, EO, TC, and revisit intention. In contrast, S/S does not moderate the relationship between DI, DA, AC and revisit intention. Meanwhile, TE significantly moderates the relationships between EO, DI, DA and revisit intention. In contrast, TE does not moderate the relationship between NO, TC, AC and revisit intention. The study's findings highlight the significance of push and pull factors, safety and security, and travel experience, with revisit intention within the MICE tourism context. This study suggests that understanding these essential factors and managing them effectively may help improve international MICE tourists’ decisions to revisit the destinations in the future. Furthermore, this study contributes new knowledge to the field of MICE tourism in Jordan and the Middle East at large. It may also serve as a potential starting point for researchers who are interested in conducting further research in this area of study.